2013
DOI: 10.1016/j.bbi.2013.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of TNFR1 and TNFR2 signaling in adult hippocampal neurogenesis

Abstract: Tumor necrosis factor alpha (TNFα) is a potent inhibitor of neurogenesis in vitro but here we show that TNFα signaling has both positive and negative effects on neurogenesis in vivo and is required to moderate the negative impact of cranial irradiation on hippocampal neurogenesis. In vitro, basal levels of TNFα signaling through TNFR2 are required for normal neural progenitor cell proliferation while basal signaling through TNFR1 impairs neural progenitor proliferation. TNFR1 also mediates further reductions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 27 publications
6
87
0
Order By: Relevance
“…Subsequent prospective studies have shown that maternal infections of various types increase the risk for schizophrenia in the offspring three-to sevenfold (for review see Brown et al, 2010). Rodent studies have confirmed that a maternal immune response is sufficient to induce psychopathology in later life (Biscaro et shown to be important for the homeostasis of neurogenesis, predominantly through the phagocytosis of apoptotic neuronal progenitor cells (Sierra et al, 2010) and balancing apoptotic and proliferative events via TNF-α signaling (Chen and Palmer, 2013). Baseline microglial activity and cytokine levels in the hippocampus are needed to maintain baseline neurogenesis while an immune response accompanied by an increase in pro-inflammatory cytokines is thought to be detrimental for neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent prospective studies have shown that maternal infections of various types increase the risk for schizophrenia in the offspring three-to sevenfold (for review see Brown et al, 2010). Rodent studies have confirmed that a maternal immune response is sufficient to induce psychopathology in later life (Biscaro et shown to be important for the homeostasis of neurogenesis, predominantly through the phagocytosis of apoptotic neuronal progenitor cells (Sierra et al, 2010) and balancing apoptotic and proliferative events via TNF-α signaling (Chen and Palmer, 2013). Baseline microglial activity and cytokine levels in the hippocampus are needed to maintain baseline neurogenesis while an immune response accompanied by an increase in pro-inflammatory cytokines is thought to be detrimental for neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…T cells, microglia, and their secreted components have been shown to alter the properties of NSC or neural progenitor/ precursor cell (NPC) populations (9,(13)(14)(15)(16)(17). Both activated microglia and some of their secreted factors such as TNF-a and IL-6 have been previously described to inhibit neuron production both in vitro and in vivo (17,18). Similarly, cytokines/chemokines and other pro-and anti-inflammatory molecules have been shown to regulate NSC/NPC survival, proliferation, fate, and migration (reviewed in Ref.…”
mentioning
confidence: 99%
“…Although EGF expands the pool of radial glia-like neural stem cells on the expense of neurogenesis, betacellulin (BTC), a member of the EGF family, induces expansion of neuroblastoma -spinal cords (NSCs) and neuroblasts, and promotes neurogenesis in the OB and dentate gyrus (Kuhn et al 1997;Gomez-Gaviro et al 2012;Lindberg et al 2012a,b). Tumor necrosis factor a (TNF-a) signaling has both positive and negative effects on neurogenesis in vivo, because TNF receptor (TNFR)-1 and TNF-a-deficient animals have elevated baseline neurogenesis in the hippocampus, whereas absence of TNFR-2 decreases baseline neurogenesis (Chen and Palmer 2013). Other peptide factors, such as FGF-2, VEGF, and pituitary adenylate cyclase-activating polypeptide (PACAP) show both proliferative and neurotrophic activity Mercer et al 2004;Schänzer et al 2004;Ohta et al 2006;Fournier et al 2012).…”
Section: Neurotrophic Factors and Growth Factorsmentioning
confidence: 99%